Sikap terhadap Etnis Tiongoha: Peran Keyakinan Konspiratif dan Kontak Antarkelompok - Audi Ahmad Rikardi; Rahmasari Dinar Mahargi; Zulfata Ziad Ma'ruf; Suwanda Priyadi (Psychopolytan : Jurnal Psikologi, 2025)
One of the social problems in Indonesia is prejudice, including against minority ethnicities, such as Chinese. One of the factors that is understudied is conspiracy beliefs, especially conspiracy beliefs related to the Chinese, which have been emerging. This study aims to explore the role of conspiracy theory beliefs and intergroup contact on prejudice towards the Chinese ethnic group. The research uses a quantitative correlational design which involved 88 participants recruited conveniently (Mage = 20.25 years), with 66% having Chinese their relatives. Data analysis conducted with multiple linear regression shows that both conspiracy theory beliefs and intergroup contact have a simultaneous role as significant predictors of prejudice towards the Chinese (R2 = 31%, F (2, 85) = 18.68, p < 0.001). Partially, conspiracy belief has a significant role in predicting prejudice against the Chinese (B = 0.36, SE = 0.07, t = 3.61, p < 0.001); meanwhile, intergroup contact has no significant role in predicting prejudice against the Chinese (B = -2.51, SE = 1.43, -1.76, p = 0.082). These results contribute to the understanding of intergroup relations, which can be explained by beliefs in conspiracy theories.